Id, Ego, and Superego in The Movie John Wick (2014): A Character Analysis - Marcelina, Hana Tasya Mei; Juanda (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This study analyzes the character of John Wick in the film